Genetically engineered macrophages persist in solid tumors and locally deliver therapeutic proteins to activate immune responses. Issue 2 (28th October 2020) - Brempelis, Katherine J; Cowan, Courtney M; Kreuser, Shannon A; Labadie, Kevin P; Prieskorn, Brooke M; Lieberman, Nicole A P; Ene, Chibawanye I; Moyes, Kara W; Chinn, Harrison; DeGolier, Kole R; Matsumoto, Lisa R; Daniel, Sara K; et al.
Abstract : Background: Though currently approved immunotherapies, including chimeric antigen receptor T cells and checkpoint blockade antibodies, have been successfully used to treat hematological and some solid tumor cancers, many solid tumors remain resistant to these modes of treatment. In solid tumors, the development of effective antitumor immune responses is hampered by restricted immune cell infiltration and an immunosuppressive tumor microenvironment (TME). An immunotherapy that infiltrates and persists in the solid TME, while providing local, stable levels of therapeutic to activate or reinvigorate antitumor immunity could overcome these challenges faced by current immunotherapies. Methods: Using lentivirus-driven engineering, we programmed human and murine macrophages to express therapeutic payloads, including Interleukin (IL)-12. In vitro coculture studies were used to evaluate the effect of genetically engineered macrophages (GEMs) secreting IL-12 on T cells and on the GEMs themselves. The effects of IL-12 GEMs on gene expression profiles within the TME and tumor burden were evaluated in syngeneic mouse models of glioblastoma and melanoma and in human tumor slices isolated from patients with advanced gastrointestinal malignancies. Results: Here, we present a cellular immunotherapy platform using lentivirus-driven genetic engineering of human and mouse macrophages to constitutively express proteins, including secreted cytokines and full-length checkpoint antibodies, as well as cytoplasmic and surface proteins that overcomes these barriers. GEMs traffic to, persist in, and express lentiviral payloads in xenograft mouse models of glioblastoma, and express a non-signaling truncated CD19 surface protein for elimination. IL-12-secreting GEMs activated T cells and induced interferon-gamma (IFNγ) in vitro and slowed tumor growth resulting in extended survival in vivo. In a syngeneic glioblastoma model, IFNγ signaling cascades were also observed in mice treated with mouse bone-marrow-derived GEMs secreting murine IL-12. These findings were reproduced in ex vivo tumor slices comprised of intact MEs. In this setting, IL-12 GEMs induced tumor cell death, chemokines and IFNγ-stimulated genes and proteins. Conclusions: Our data demonstrate that GEMs can precisely deliver titratable doses of therapeutic proteins to the TME to improve safety, tissue penetrance, targeted delivery and pharmacokinetics.